SYSTEM RELIABILITY ASSESSMENT ON EXISITING JACKET PLATFORMS IN MALAYSIAN WATERS - VOON, MIN CHHIN (2014)
Oil and Gas Industry as majority of the jacket platforms in Malaysian waters to date, have exceeded their design life. Reliability of a jacket platform can be evaluated through Structural Reliability Analysis. Conventional metocean consideration uses 100 year return period wave height associated with 100 year return period current velocity and wind speed. However, recent studies show that for Malaysian waters, the proposed metocean consideration should be 100 year return period wave height associated with 10 year return period current velocity and wind speed. Hence, this research studies the effect of different metocean considerations to system based reliability of the jacket platforms in Malaysian waters. Besides, the significance of parameters such as metocean considerations, pile soil interaction (PSI), and environmental load direction are observed in a sensitivity study in